A Novel Antimicrobial Peptide (Kassinatuerin-3) Isolated from the Skin Secretion of the African Frog, Kassina senegalensis - Hui Wang (Biology, 2020)
Amphibian skin secretions are remarkable sources of novel bioactive peptides. Among these, antimicrobial peptides have demonstrated an outstanding efficacy in killing microorganisms via a general membranolytic mechanism, which may offer the prospect of solving specific target-driven antibiotic resistance. Here, the discovery of a novel defensive peptide is described from the skin secretion of the African frog, Kassina senegalensis. Named kassinatuerin-3, it was identified through a combination of “shot-gun” cloning and MS/MS fragmentation sequencing. Subsequently, a synthetic replicate was subjected to biofunctional evaluation. The results indicated that kassinatuerin-3 possessed antimicrobial activity against Gram-positive bacteria but no effect against Gram-negative bacteria. Additionally, it was active in biofilm eradication on S. aureus and MRSA and in the antiproliferation of selected cancer cell lines. Moreover, it had a very mild hemolytic effect, which demonstrated a high therapeutic index for kassinatuerin-3. Collectively, although kassinatuerin-3 did not demonstrate remarkable bioactivities compared with other natural or synthetic antimicrobial peptides (AMPs), it offered a new insight into the design of antimicrobial derivatives.